Penyuluhan Tata Laksana Penanganan Pasien Pasca Cedera sebagai Upaya Pelayanan Kesehatan pada Siswa-Siswi SMK di Wilayah Kecamatan Krian - Atmaja, Danuditya Purna; Ghurri, Ainul; Andriana, Laily Mita; Rosanti, Dwike Primadita; Ningrum, Selfya (Jurnal Pengabdian Kepada Masyarakat, 2024)
Sports injuries are injuries that occur during training, competition or after exercise. Sports injuries occur due to the inability of tissues (muscles, joints, tendons, skin) and other organs to receive training loads during exercise. Factors that influence the occurrence of injuries, namely individual conditions (age, gender, character, experience, warm-up, posture abnormalities), sports facilities (shape and size of equipment), sports characteristics (type of sport), physical environment (temperature and humidity). If not treated immediately, it can cause cerebral vascular disorders (heat stroke) and immediately do an examination if you experience an injury during exercise, so that you can get fast and proper treatment. On this occasion, lecturers from the Faculty of Health Sciences, Anwar Medika University (UAM) Sidoarjo held counseling activities for vocational students in the Krian Sidoarjo sub-district area. The purpose of this counseling is expected so that later SMK students can play an active role in conveying and implementing the knowledge in this activity to help the community around their place of residence.